The Use of AI by Elementary Teacher Education Students: Between Innovation and Dependency - Rambe, Nurhamimah (Journal of Classroom Action Research, 2025)
This study aims to analyze the use of Artificial Intelligence (AI) by fourth-semester students of the Primary School Teacher Education (PGSD) program in completing academic assignments. Specifically, the study explores (1) the impact of AI use on students' critical thinking skills, (2) students' perceptions of AI's role in academic tasks, (3) the extent to which AI influences the quality of academic assignments, and (4) the ethical implications of AI use in the training of future teachers. Employing a quantitative survey approach and qualitative thematic analysis from 77 respondents, it was found that AI has become a prevalent and highly valued tool due to its ability to enhance efficiency and save time in various academic tasks (e.g., essay writing, summarizing, presentations). However, findings also indicate an increased dependence on AI, raising concerns about a potential decline in critical thinking skills and intellectual laziness. While AI is perceived to improve assignment professionalism and facilitate achieving higher grades, students consistently emphasize the need for extensive revision of AI output to ensure accuracy, originality, and adherence to academic standards. Furthermore, significant ethical implications related to plagiarism, academic dishonesty, and the potential for superficial learning are major concerns among students, who actively advise using AI as a tool that requires critical verification, rather than a substitute for independent thought. This study concludes that the integration of AI in future teacher education must be done wisely and responsibly, emphasizing the importance of academic integrity, continuous critical thinking development, and intellectual autonomy to prepare competent and ethical future educators. This study recommends that AI integration in teacher education emphasize academic integrity, foster continuous critical thinking, and ensure intellectual autonomy